International law as a political instrument in the case of Kosovo (1999-2010) - Jasper E. Bergink (Amsterdam Law Forum, 2010)
<!--StartFragment--> The article attempts to integrate international law and international relations by analysing how law works within international politics. In international relations, the instrumentalist theory poses that states rationally employ international law as a foreign policy instrument. Analysing the case of Kosovo from 1999 to 2010, this article aims to show what international law really does. It highlights the indeterminacy or imprecision of law as a feature that hinders its effectiveness. Moreover, it argues that law’s discursive function and the final consequences of the use of law should be analysed to judge the claims of instrumentalism. <!--EndFragment-->